2005
DOI: 10.1124/dmd.105.004630
|View full text |Cite
|
Sign up to set email alerts
|

BIOTRANSFORMATION OF A GABAARECEPTOR PARTIAL AGONIST IN SPRAGUE-DAWLEY RATS AND CYNOMOLGUS MONKEYS: IDENTIFICATION OF TWO UNIQUEN-CARBAMOYL METABOLITES

Abstract: ABSTRACT:The The presence of M8 in bile and its notable absence from other matrices suggests the enterohepatic cycling of 1 via M8. Although the structure of M7 was not elucidated unequivocally due to its inability to be formed in vitro and its minimal absolute quantities in limited biological matrices, data herein clearly support its structural rationalization. Furthermore, since M7 is the precursor of M8, detection of M8 is indirect evidence of its existence. It is proposed that M7 arises from an equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
2
30
0
1
Order By: Relevance
“…Active renal secretion of 1 was observed as its unbound CL R was 6-fold greater than the glomerular filtration rate (GFR) ( Table 3), consistent with the identification of 1 as a multidrug resistance 1 P-glycoprotein substrate (Venkatakrishnan et al, 2007) and the established contribution of this transporter to active renal secretion of its substrates (Lee and Kim, 2004). A similar extent of active renal secretion was observed in monkeys (6ϫ GFR) but not rats (2ϫ GFR) (Shaffer et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Active renal secretion of 1 was observed as its unbound CL R was 6-fold greater than the glomerular filtration rate (GFR) ( Table 3), consistent with the identification of 1 as a multidrug resistance 1 P-glycoprotein substrate (Venkatakrishnan et al, 2007) and the established contribution of this transporter to active renal secretion of its substrates (Lee and Kim, 2004). A similar extent of active renal secretion was observed in monkeys (6ϫ GFR) but not rats (2ϫ GFR) (Shaffer et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…However, the size of this contribution was undeterminable because it was unknown how much of 1 (if any) detected in feces was actually absorbed following ingestion. Biliary clearance of 1 was minimal in both rats and monkeys (Shaffer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…7, A and B), which confirmed that M24 was a glucuronide metabolite. Although the carbamic acid intermediate was not observed in the incubation mixture by LC/MS/MS because of the instability of this species (Shaffer et al, 2005;Gunduz et al, 2010), the fragmentation of M24 has the signature fragmentation pattern of N-carbamoyl glucuronides, which produced the product ion of m/z 413, 44 Da higher than the parent drug (Dow et al, 1994;Liu et al, 2001;Shaffer et al, 2005;Gunduz et al, 2010). The exact mass measurement confirmed that M24 is a carbamoyl glucuronide of C and D).…”
Section: Disposition Of Bms-690514 In Rats Dogs and Rabbitsmentioning
confidence: 85%
“…17) It has been proposed that the mechanism that generates these glucuronides starts by forming carbamic acid as an intermediate under physiological conditions in the liver through a reversible reaction with CO 2 dissolved in the environmental fluid. 13,[18][19][20][21][22] UDP-glucuronyl transferase (UGT) then causes the immediate conjugation of this carbamic acid with glucuronic acid by utilizing UDPglucuronic acid as a cofactor. Recent studies using recombinant human enzymes suggest that UGT2B7, UGT1A3, UGT2B4, and UGT1A6 may be the UGT isozymes responsible for the formation of sertraline carbamoyl glucuronide, 21) and UGT2B7 for the formation of varenicline carbamoyl glucuronide.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the slow rotation of the carbonyl glucuronic acid moiety at the C-N bond of the carbamate. 13) An overview of the postulated metabolic pathways of this drug in mice is shown in Fig. 4.…”
Section: Identification Of An Unknown Biliary Metabolitementioning
confidence: 99%